PENGARUH JENIS KELAMIN DAN PENGETAHUAN LINGKUNGAN TERHADAP PENILAIAN BUDAYA LINGKUNGAN (Studi Ex Post Facto di Akademi Manajemen Informatika dan Komputer Bina Sarana Informatika Jakarta) - Dahlia Sarkawi (Universitas Bina Sarana Informatika, 2012)
This study aimed to determine the effect of gender and environmental science students to the assessment of environmental culture. A quantitative research methods Ex Post Facto in Akademi Manajemen Informatika dan Komputer Bina Sarana Informatika (AMIK BSI), Jakarta in 2012.Methods of data collection conducted through a questionnaire for assessment of gender and cultural environment as well as tests for environmental knowledge. Analysis and interpretation of the data concluded that there are significant differences in the cultural assessment scores on male students to female students. Second, the group of students with high environmental knowledge, there is no difference between male students with assessments of women's cultural environment. Third, the group of students who have a low environmental knowledge, there is a difference between male students to female in assessing cultural environment. Fourth, there is no interaction between sex of men with women, and knowledge of the cultural environment on student assessment.The study recommends the importance of environmental knowledge to create environmental assessment of student culture. Therefore, efforts need to be programmed and sustainable environmental education given among students.Keywords: sex, environmental knowledge, cultural environment.